Live high, train smart: translating altitude physiology to best practice with mechanistic insights - Faiss, R.; Girard, O. (Frontiers in Physiology, 2026)
The first symposium on altitude training took place 60 years ago in Magglingen (Switzerland), where preparation for the 1968 Mexico Olympic Games provided "an excellent opportunity for the study of human adaptability" in hypoxic environments. Decades later, altitude or hypoxic training blocks -discrete periods (typically days to weeks) during which athletes reside, train, or intermittently expose themselves to hypoxia to stimulate physiological adaptations-have become a common component of elite endurance and team-sport training. Traditional strategies such as "live high-train high" and "live high-train low" have largely been adopted to stimulate erythropoiesis. The principal performance target is an increase in total hemoglobin mass (tHbmass), thereby enhancing O2 delivery to the working muscles through a higher arterial oxygen content. Despite ongoing debate regarding the precise physiological mechanisms underpinning altitude training adaptations, many key lessons were learned in the past 25 years related to hypoxic dose, exposure timing, and inter-individual variability in adaptative responses. Reflecting sustained scientific interest, no less than 12 comprehensive reviews or meta-analyses on altitude training strategies have been published in the past five years alone. These studies consistently report erythropoietic adaptations to hypoxia while seeking to refine practical recommendations regarding the optimal altitude severity and duration of exposure to potentiate increases in tHbmass. In this perspective article, potential vectors of performance improvement associated with hypoxic/altitude training were reconceptualized. By mapping contemporary altitude training strategies alongside their respective physiological mechanisms, we propose a framework that may help guide evidence-informed practice for research end-users seeking to boost their performance.